Identifying the Molecular Mechanisms and Types of Cell Death Induced by bio- and pyr-Silica Nanoparticles in Endothelial Cells - Solarska-Ściuk, Katarzyna; Adach, Kinga; Fijałkowski, Mateusz; Haczkiewicz-Leśniak, Katarzyna; Kulus, Michał; Olbromski, Mateusz; Glatzel-Plucińska, Natalia; Szelest, Oskar; Bonarska-Kujawa, Dorota (International journal of molecular sciences, 2022)
The term "nanosilica" refers to materials containing ultrafine particles. They have gained a rapid increase in popularity in a variety of applications and in numerous aspects of human life. Due to their unique physicochemical properties, SiO2 nanoparticles have attracted significant attention in the field of biomedicine. This study aimed to elucidate the mechanism underlying the cellular response to stress which is induced by the exposure of cells to both biogenic and pyrogenic silica nanoparticles and which may lead to their death. Both TEM and fluorescence microscopy investigations confirmed molecular changes in cells after treatment with silica nanoparticles. The cytotoxic activity of the compounds and intracellular RNS were determined in relation to HMEC-1 cells using the fluorimetric method. Apoptosis was quantified by microscopic assessment and by flow cytometry. Furthermore, the impact of nanosilica on cell migration and cell cycle arrest were determined. The obtained results compared the biological effects of mesoporous silica nanoparticles extracted from Urtica dioica L. and pyrogenic material and indicated that both types of NPs have an impact on RNS production causing apoptosis, necrosis, and autophagy. Although mesoporous silica nanoparticles did not cause cell cycle arrest, at the concentration of 50 μg/mL and higher they could disturb redox balance and stimulate cell migration.
Keywords: oxid křemičitý; Apoptosis; Nanoparticles; silica nanoparticles; Necrosis; cell death; apoptóza; lidé; Silicon Dioxide; nekróza; oxidative stress; cell migration; Endothelial Cells; HMEC-1; endoteliální buňky; nanočástice; Humans